Early life feeding accelerates gut microbiome maturation and suppresses acute post‐weaning stress in piglets. (16th October 2021) - Choudhury, R.; Middelkoop, A.; Boekhorst, J.; Gerrits, W. J. J.; Kemp, B.; Bolhuis, J. E.; Kleerebezem, M.
Summary: Early life microbiome perturbations can have important effects on host development, physiology and behaviour. In this longitudinal study, we evaluated the impact of early feeding on gut microbiome colonization in neonatal piglets. Early‐fed (EF) piglets had access to a customized fibrous diet from 2 days after birth until weaning in addition to mother's milk, whereas control piglets suckled mother's milk only. Rectal swabs were collected at multiple time points until 6 weeks of age to investigate microbiota development using 16S rRNA gene profiling. The dynamic pre‐weaning microbiota colonization was followed by a relatively stable post‐weaning microbiota, represented by Prevotella, Roseburia, Faecalibacterium, Ruminococcus, Megasphaera, Catenibacterium and Subdoligranulum . EF piglets showed an accelerated microbiota maturation, characterized by increased microbial diversity, pre‐weaning emergence of post‐weaning‐associated microbes and a more rapid decline of typical pre‐weaning microbes. Furthermore, the individual eating behaviour scores of piglets quantitatively correlated with their accelerated microbiome. Importantly, EF piglets displayed a smoother relative weight gain and tended to reach a higher relative weight gain, in addition to reduced diarrhoea scores in the first week post‐weaning. Overall, these findings demonstrate the beneficial impact of early feeding on microbiota development as well as pig health and performance during the weaning transition.